Effect of iron hydroxide on phosphate removal during anaerobic digestion of activated sludge - Stabnikov, Victor; Tay, Stephen; Tay, Joo; Ivanov, Volodymyr M. (My University, 2004)
Addition of ferric hydroxide to the reactor of methanogenic fermentation of activated sludge followed microbial reduction of Fe (III) and formation of ferrous ions, which precipitated phosphate. It was shown that 66.6 – 99.6 % of dissolved phosphate with initial concentration of 1000 – 3500 mg РО43-/l can be removed by the addition of ferric hydroxide in concentration of 6420 mg Fe (III)/l and anaerobic sludge with iron-reducing activity. Optimal ratio of added Fe(III): removed dissolved phosphate, ensured not less than 95 % removal of phosphate was 2. These data could be used in a new technology of anaerobic treatment of wastewater with simultaneous removal of phosphate.
Keywords: ferric hydroxide; activated sludge; removal of phosphate; iron-reducing activity; гідроокис заліза; активний мул; фосфати; залізовідновлювальна активність; кафедра біотехнології і мікробіології